2004
DOI: 10.1517/14656566.5.8.1781
|View full text |Cite
|
Sign up to set email alerts
|

Anagrelide: a decade of clinical experience with its use for the treatment of primary thrombocythaemia

Abstract: Primary thrombocythaemia (PT) is the most frequent among the rare chronic myeloproliferative disorders. Life expectancy is determined by thromboembolic and haemorrhagic complications, which can be prevented by cytoreductive therapy. For a long time, hydroxyurea has been considered as the therapeutic gold standard. However, hydroxyurea treatment is not lineage-specific, may not be tolerated because of adverse effects (skin, gastrointestinal tract) and is leukaemogenic when sequentially used with other DNA-targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Given the long duration of use of these multiple agents and the duration of the primary disease itself, it was not unexpected that this patient had leukemic transformation. The other 2 patients received a combination of HU, anagrelide and interferon (IFN) for 4 and 14 years before LT. To date, anagrelide is not mutagenic 23 and there is no evidence suggesting that it is leukemogenic 22 . Interferon is also not known to be leukemogenic 22 .…”
Section: Discussion (I) Incidence Of Leukemic Transformation (Lt) Andmentioning
confidence: 99%
“…Given the long duration of use of these multiple agents and the duration of the primary disease itself, it was not unexpected that this patient had leukemic transformation. The other 2 patients received a combination of HU, anagrelide and interferon (IFN) for 4 and 14 years before LT. To date, anagrelide is not mutagenic 23 and there is no evidence suggesting that it is leukemogenic 22 . Interferon is also not known to be leukemogenic 22 .…”
Section: Discussion (I) Incidence Of Leukemic Transformation (Lt) Andmentioning
confidence: 99%
“…6,29 More recently, mainly because of concern about the leukemogenic potential of HC, 32 ANA has also become widely used. 25,26,[33][34][35] However, the choice between the two drugs is often uncertain. Results from a recent clinical trial comparing HC and ANA in high-risk ET patients showed an increased frequency of vascular events and more cases progressing to myelofibrosis in the ANA group.…”
Section: Discussionmentioning
confidence: 99%
“…Anagrelide is not mutagenic [74], and there is no known evidence to suggest that it is leukaemogenic [75]. In a longterm retrospective analysis, anagrelide did not result in excess conversion to AML, and no ET patient receiving anagrelide for more than 3 years transformed [64].…”
Section: Anagrelidementioning
confidence: 95%